Social Networks with Rich Edge Semantics - Zheng, Quan (Taylor & Francis, 2017)
This book introduces a new mechanism for representing social networks in which pairwise relationships can be drawn from a range of realistic possibilities, including different types of relationships, different strengths in the directions of a pair, positive and negative relationships, and relationships whose intensities change with time. For each possibility, the book shows how to model the social network using spectral embedding. It also shows how to compose the techniques so that multiple edge semantics can be modeled together. The modeling techniques are then applied to a range of datasets to show how they can produce results that are useful in understanding real-world social networks.